2015
DOI: 10.1017/s1474745615000464
|View full text |Cite
|
Sign up to set email alerts
|

Nature and Enforceability of WTO-plus SPS and TBT Provisions in Canada's PTAs: FromNAFTAtoCETA

Abstract: Safety standards can function as non-tariff barriers to trade. Canada is a large exporter of goods and so it has an interest in the regulation of safety standards, both at the multilateral level through its membership of the World Trade Organization (WTO) and, most especially, at the bilateral and regional level through its Preferential Trade Agreements (PTAs). Canada has signed PTAs with provisions that go beyond the obligations of WTO Members under the Agreement on the Application of Sanitary and Phytosanita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The literature on the institutional design of SPS chapters includes both, detailed case studies and large-N studies. The case studies often focus on specific countries or regions such as the EU (Rudloff and Simons, 2004), Canada (Puig and Dalke, 2016), or Asia (Kleimann, 2014) as well as cross-regional comparisons such as, for instance, between North American and European PTAs (von Lampe and Jeong, 2013).…”
Section: The Design Of Sps Chaptersmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on the institutional design of SPS chapters includes both, detailed case studies and large-N studies. The case studies often focus on specific countries or regions such as the EU (Rudloff and Simons, 2004), Canada (Puig and Dalke, 2016), or Asia (Kleimann, 2014) as well as cross-regional comparisons such as, for instance, between North American and European PTAs (von Lampe and Jeong, 2013).…”
Section: The Design Of Sps Chaptersmentioning
confidence: 99%
“…Similarly to the literature on SPS measures in PTAs, the literature on the governance of TBT-related issues in PTAs includes regional case studies on, for instance, African PTAs (Meyer et al, 2010), Asian PTAs (Kleimann, 2014), and Canadian PTAs (Puig and Dalke, 2016) as well as large-N studies.…”
Section: The Design Of Tbt Chaptersmentioning
confidence: 99%
“…to what extent the PTAs create rules that go beyond the WTO legal status quo 8 . Villalta Puig and Dalke (2016) apply the HMS methodology to analyze the legal enforceability of sanitary and phytosanitary measures (SPS) and technical barriers to trade (TBT) provisions in Canada's PTAs. Kohl et al (2016) focus on 13 WTO+ and 4 WTO-X provisions identified by HMS and expand the coverage of preferential trade agreements to 296 9 .…”
Section: The New Database: Coverage and Legal Issuesmentioning
confidence: 99%
“…Differently from HMS and WTR 2011, we investigate a much broader sample of PTAs. Also differently from Kleimann (2014), Villalta Puig and Dalke (2016), and Kohl et al (2016), the new database assesses the coverage of an extended set of policy areas in PTAs, and is not focused on a selected number of provisions. This latter feature allows us to investigate in Sections 3 and 4 the non-core provisions in PTAs, the broader scope of trade agreements, the similarities/differences in content across PTAs by income and geography groups, and the impact of deep PTAs on trade flows.…”
Section: The New Database: Coverage and Legal Issuesmentioning
confidence: 99%